Performance Enhancement of Crystal Silicon Solar Cell by a CsPbBr3–Cs4PbBr6 Perovskite Quantum Dot @ZnO/Ethylene Vinyl Acetate Copolymer Downshifting Composite Film. Issue 11 (31st August 2022) - Song, Jian; Ren, Yifan; Gong, Shijie; Zhao, Liang; Xuan, Wufan; Zhu, Lei; Zhao, Yulong; Qiang, Yinghuai; Gao, Lili; Huang, Sheng
Abstract : Crystal silicon solar cells being the most successful photovoltaic devices have prevailed in the energy market for decades. To further improve the device performance, photon management is necessary. Herein, a CsPbBr3 –Cs4 PbBr6 perovskite quantum dot@ZnO/ethylene vinyl acetate copolymer downshifting composite film is coated on the silicon solar cell. This downshifting composite film helps to convert high‐energy (UV‐blue) photons to relatively low‐energy photons with a wavelength at about 500 nm, which possess higher sensitivity in silicon solar cells. The effects of tetra‐ n ‐heptylammonium bromide and Zn(C2 H5 )2 on composition, optical and luminescence properties of perovskite quantum dots are thoroughly investigated, and a clean quantum dot solution with strong luminescent intensity can be obtained. The perovskite quantum dot@ZnO/ethylene vinyl acetate composite film absolutely improves the efficiency of silicon solar cells by 1.18%. The value is much higher than pure ethylene vinyl acetate (0.42%) and composite film without ZnO (0.57%). Moreover, ZnO inclusion can inhibit Cs and Pb leakage and maintain the device working stability, which is helpful for their commercial application in the future. This study further reveals that the enhancement lies in carrier relaxation energy loss reduction. Herein, a low‐cost downshifting composite film with excellent environmental stability for silicon solar cells applications is proposed. Abstract : A stable ZnO‐protected CsPbBr3 –Cs4 PbBr6 perovskite quantum dot/ethylene vinyl acetate copolymer downshifting composite film at room temperature for crystal silicon solar cell is proposed. It can absolutely improve the device efficiency by 1.18%. Calculation results reveal that the enhancement mainly lies in carrier relaxation energy loss reduction. This work is meaningful in exploiting the potential for commercial photovoltaic devices.